Pro ODP .NET for Oracle Database 11g - Zehoo, Edmund; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
This book is a comprehensive and easy-to-understand guide for using the Oracle Data Provider (ODP) version 11g on the .NET Framework. It also outlines the core GoF (Gang of Four) design patterns and coding techniques employed to build and deploy high-impact mission-critical applications using advanced Oracle database features through the ODP.NET provider. The book details the features of the ODP.NET provider in two main sections: (3z(BBasic,(3y (Bcovering the basics and mechanisms for data access via ODP.NET; and (3z(BAdvanced,$1 (Bcovering advanced Oracle features such as globalization, savepoints, distributed transactions and how to call them via ODP.NET, advanced queueing (AQ), and promotable transactions. It takes you from the ground up through different implementation scenarios via a rich collection of C# code samples. It outlines database security and performance optimization tricks and techniques on ODP.NET that conform to best practices and adaptable design. Different GoF design patterns are highlighted for different types of ODP.NET usage scenarios with consideration of performance and security. It provides a comprehensive guide to the synergistic integration of Oracle and Microsoft technologies such as the Oracle Developer Tools for Visual Studio (11.1.0.7.10). It also details how programmers can make use of ODT to streamline the creation of robust ODP.NET applications from within the Visual Studio environment.s
to Oracle .NET Connectivity -- ODP.NET: A Functional Overview -- Connecting to Oracle with ODP.NET -- Retrieving and Manipulating Data with ODP.NET -- Using PL/SQL and .NET CLR Stored Procedures with ODP.NET -- ODP.NET Globalization -- Transactions with ODP.NET -- Oracle Database Change Notifications with ODP.NET -- Using Oracle Database Streams Advanced Queuing with ODP.NET -- Oracle XML Support -- ODP.NET Security Features -- ODP.NET Performance -- Design Patterns and Considerations in Using ODP.NET -- ODT.NET Tool Basics -- Building Data-Driven Applications with ODT.NET.
Keywords: Computer science; Computer Science; Programming Techniques